Common Agricultural Policy effects on dynamic labour use in agriculture - Martin Petrick; Patrick Zier (Food Policy, 2012)
The aim of this study is to investigate the effects of direct payments and rural development measures of the EU's Common Agricultural Policy (CAP) on employment in agriculture. We work with a dynamic labour demand equation augmented by the full set of policy instruments of the CAP, which is estimated on a panel dataset of 69 East German regions. We present results for four estimators which differ in how they eliminate the fixed effects and how they address the endogeneity of the lagged dependent variable. The results suggest that there were few desirable effects on job maintenance in agriculture. While there is some indication that investment subsidies have halted labour shedding on farms, a rise in the general wage level reduced labour use in agriculture. Changes in direct payments had no employment effects. Generally, labour adjustment exhibits a strong path dependency.
Keywords: Q18; J43; C23; 330; Agricultural employment; Dynamic panel data models; Common Agricultural Policy; East Germany